Evaluation Of Good Corporate Governance PT. Mazda, East Jakarta - Aisah, Siti; Tahirman, Tahirman (Jurnal Ilmiah Manajemen Kesatuan, 2023)
Career development in business development strategies and services is useful in the process of improving individual skills in order to achieve a better career. And job satisfaction shows how far individuals feel about the positive or negative aspects of all factors and dimensions of their duties in their work. The purpose of this research is to understand a person's career development in business development strategies, job satisfaction and analyze the influence of business development and services on employee job satisfaction at the East Jakarta PT Mazda office. The method used in this research is qualitative method. Based on the results of the Good Corporate Governance (GCG) evaluation in the PT. Mazda East Jakarta, there are two sections, namely 3 products, 11 services and 7 sales services.   Keywords : Good Corporate Governance